Penerapan Intervensi Edukasi Pendidikan terhadap Fatigue pada Pasien Hemodialisis - Zuliani, Peri; Irawati, Diana; Anggraeni, Dewi; Jumaiyah, Wati; Abriyanti, Rika Mustika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to implement education on fatigue in hemodialysis patients. The method used was a Randomized Controlled Trial with a quasi-experimental research design. The results showed a significant difference in the average total Fatigue score in the experimental and control groups after participating in the program (P < 0.001). There were also statistically significant differences between age, gender, disease duration, dialysis frequency, and Fatigue level (p<0.05). In conclusion, the educational intervention aims to increase knowledge so that patients can comply with the educational intervention provided and can help reduce fatigue levels in patients undergoing hemodialysis. Keywords: CKD, Education, Fatigue